Formal methods : foundations and applications : 20th Brazilian Symposium, SBMF 2017, Recife, Brazil, November 29-December 1, 2017, Proceedings /: foundations and applications : 20th Brazilian Symposium, SBMF 2017, Recife, Brazil, November 29-December 1, 2017, Proceedings. (2017) - Unknown
No abstract available